What Is Going Through Your Mind? Thinking Aloud as a Method in Cross-Cultural Psychology - Güss, C. Dominik (Frontiers in Psychology, 2018)
Thinking aloud is the concurrent verbalization of thoughts while performing a task. The study of thinking-aloud protocols has a long tradition in cognitive psychology, the field of education, and the industrial-organizational context. It has been used rarely in cultural and cross-cultural psychology. This paper will describe thinking aloud as a useful method in cultural and cross-cultural psychology referring to a few studies in general and one study in particular to show the wide applications of this method. Thinking-aloud protocols can be applied for a) improving the validity of cross-cultural surveys, b) process analysis of thoughts and the analysis of changes over time, c) theory development across cultures, d) the study of cultural meaning systems, and e) individual as well as group level analyses allowing hypothesis testing cross-culturally. Limitations of the thinking-aloud method are also discussed.